Impact of SCOR Model on Firm’s Supply Chain Performance - A Case Study Method: IMPACT OF SCOR MODEL (KASBIT Business Journal, 2023)
Customers' preferences increase daily in the global market today, where competition is high. Therefore, factors such as cost, quality, innovation and reliability are the key factors affecting the overall effectiveness of the enterprise. Developed on the foundation of existing literature, a theoretical basis was created, and preliminary data were collected from 30 participants at Atlas Battery Limited. After data collection, the hypotheses were tested using statistical tools. Data was collected using a survey of Atlas Battery Limited participants, and correlation analysis was used to analyze the relationship between the SCOR model and supply chain performance. Results show a statistically significant relationship between the SCOR model and supply chain performance. This study shows that the SCOR model is very important to any organization to achieve market competitive advantage and increase the overall efficiency of the organization. The results of this study can help supply chain specialists understand the impact of the SCOR model on supply chain performance. Along with quality, reliability, responsiveness and cost, they play a very important role in meeting customer needs, which should be the ultimate goal of any organization if they want to grow.
Keywords: Supply Chain Operations Reference (SCOR) model; Supply Chain Performance Metrics (SCPM); Supply Chain Performance (SCP)